2009
DOI: 10.1063/1.3275742
|View full text |Cite
|
Sign up to set email alerts
|

Observation of hypersonic phononic crystal effects in porous silicon superlattices

Abstract: Brillouin light scattering experiments were carried out on porous silicon superlattices with modulation wavelengths in the range 37-167 nm. Phonon frequencies deduced from the Brillouin spectra show good agreement with those obtained from an elastic continuum model for a system with one-dimensional periodicity. Evidence for the existence of a hypersonic phononic bandgap and zone-folded longitudinal acoustic phonons is reported. © 2009 American Institute of Physics. ͓doi:10.1063/1.3275742͔It is well known that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 7 publications
1
30
0
Order By: Relevance
“…Additionally, theoretical and experimental studies of stacked phononic crystal mirrors 6,9 have shown the existence of giant phononic band gaps in the MHz frequency range of these structures. As well, Brillouin light scattering studies on binary periodic porous silicon (p-Si) superlattices (SLs) showed a complex bulk longitudinal acoustic band structure, 3,8 with a second longitudinal mode branch observed for phonons directed along the superlattice modulation axis. Furthermore, these light scattering experiments gave evidence of an additional Brillouin peak which was attributed to a surface-localized mode with a frequency within a one-dimensional hypersonic phononic band gap of the bulk longitudinal band structure centered at $16 GHz.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, theoretical and experimental studies of stacked phononic crystal mirrors 6,9 have shown the existence of giant phononic band gaps in the MHz frequency range of these structures. As well, Brillouin light scattering studies on binary periodic porous silicon (p-Si) superlattices (SLs) showed a complex bulk longitudinal acoustic band structure, 3,8 with a second longitudinal mode branch observed for phonons directed along the superlattice modulation axis. Furthermore, these light scattering experiments gave evidence of an additional Brillouin peak which was attributed to a surface-localized mode with a frequency within a one-dimensional hypersonic phononic band gap of the bulk longitudinal band structure centered at $16 GHz.…”
mentioning
confidence: 99%
“…Multilayered mesoporous silicon films with a spatial modulation in the porosity, and hence in the elastic impedance, exhibit rich acoustic phonon band structures. [1][2][3][4][5][6][7][8][9][10] The resulting bulk acoustic dispersion curves contain multiple zone-folded branches which may be accompanied by the appearance of forbidden phonon frequency bands, or in analogy to photonic crystals, phononic band gaps. Recent ultrasonic measurements along the modulation direction of films with square-wave, 4,7 sinusoidal, 5 and linearly graded modulation 10 variations in the porosity have reported the existence of one-dimensional phononic band gaps in the bulk longitudinal acoustic phonon band structure; these band gaps were centered at frequencies on the order of 1 GHz.…”
mentioning
confidence: 99%
“…Experiments were also done on two porous silicon films made from p + -type (100)-oriented crystalline silicon under conditions similar to those given in Ref. 10. The films were ∼4.5 μm thick and had porosities of (58 ± 3)% and (50 ± 4)%.…”
Section: Methodsmentioning
confidence: 99%
“…1,[8][9][10] Unfortunately, this geometry allows access to bulk phonons of only a single wavevector magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…Among these applications, one can mention (1) omnidirectional band gaps [55][56][57][58], (2) the possibility to engineer small-size sonic crystals with locally resonant band gaps in the audible frequency range [59], (3) hypersonic crystals [60][61][62][63] with high-frequency band gaps to enhance acousto-optical [49][50][51] or optomechanical [64,65] interaction and to realize stimulated emission of acoustic phonons [66], and (4) the possibility to enhance selective transmission through guided modes of a cavity layer inserted in the periodic structure [6,67] or by interface resonance modes induced by the superlattice/substrate interface [68][69][70]. The advantage of 1D systems lies in the fact that their design is more feasible and they require only relatively simple analytical and numerical calculations.…”
Section: Introductionmentioning
confidence: 99%